Discussion on key technologies in micro-CT experiments and their applications in oil and gas exploration - Xiangsheng HUANG; Chengfei LUO; Qun ZHANG; Jinding CHEN; Yaoyuan ZHANG; Xiaowen LIU (Shiyou shiyan dizhi)
Micro-CT technology has been widely applied in oil and gas exploration and development. However, unified standards for key control parameters and data processing methods have yet to be established, significantly affecting data accuracy and comparability. To systematically study the impact of micro-CT experimental parameters on test results, seven representative samples from the Beibuwan Basin and the Yinggehai Basin in the South China Sea were used as the research subjects. The research focused on the impact of scanning resolution, representative volume element (RVE) size, and data processing methods on experimental outcomes. The findings indicated that: (1) A fixed scanning resolution is a key factor in ensuring data reliability, as it significantly affects the extraction of pore structure parameters and subsequent analysis. Resolution should be optimized considering sample size and lithological characteristics. (2) For characterizing the porosity of sandstone samples, better result accuracy can be achieved by increasing the RVE size. While constructing pore network models, the RVE size should be no smaller than 600×600×600 voxels to ensure model representativeness. (3) Use interval-based statistics to calculate the cumulative volume frequency of pore diameters (Φ), and plot the pore size distribution curves. Use the volumetric method to calculate the average pore diameter. These methods can provide a more accurate characterization of rock pore structure. The study offers theoretical support for the application and workflow optimization of micro-CT technology in oil and gas exploration, providing a reference for establishing experimental standards.